The Use of the Course Review Horay Learning Model with Bingo Media to Improve Students' Understanding of Islamic Religious Education Learning Materials - Indri Retno Wijayanti; Mokh. Iman Firmansyah; Nurti Budiyanti (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
Islamic Religious Education learning plays an important role in shaping students' religious understanding, attitudes, and behavior. However, the PAI learning process in schools still tends to be teacher-centered, so students' understanding of the material has not developed optimally. This study aims to analyze the improvement of students' understanding and to determine students' responses to the application of the Course Review Horay (CRH) learning model with Bingo media in IRE learning. This study uses a quantitative approach with a pre-experimental one-group pretest-posttest design. The research subjects consisted of 41 ninth-grade students at one of the public junior high schools in Bandung Regency. Data collection techniques were carried out through understanding tests and student response questionnaires. Data were analyzed using descriptive and inferential statistics, including the Wilcoxon Signed Rank Test and N-Gain analysis. The results showed an increase in students' understanding after the application of the CRH learning model with Bingo media. The average pretest score of 76.83 increased to 87.80 in the posttest, and all students achieved learning mastery. The Wilcoxon test showed a significant difference between the pretest and posttest scores (Asymp. Sig. 0.000 < 0.05), while the N-Gain results were in the moderate category. In addition to improving understanding, this study also provided a positive response to the implementation of this learning model, although several obstacles were still encountered in the initial stages of implementation and student learning independence. Based on these findings, it can be concluded that the Course Review Horay learning model using Bingo media is effective in improving student understanding and is suitable for use in Islamic Religious Education (PAI) learning with improvements in the management of learning implementation.